MICROFINANCE AND WOMEN MICROENTREPRENEURS: KEY VARIABLES INFLUENCING SOCIO-ECONOMIC AND FINANCIAL SUCCESS - Roy, Gourav; Sarkar, Popy Rani (Indian Journal of Finance and Banking, 2024)
As Bangladesh has almost a 49.5:50.5 ratio of male to female, the utilization of women workforce in GDP is very significant where microfinance has been enabling women to initiate microenterprises since 1974. That microfinance can contribute to the socio-economic and entrepreneurial financial success of women required proper investigation. This study examines whether microfinance impacts the socio-economic development of women microentrepreneurs and whether microfinance impacts the financial performance of women-led microenterprises. This primary and secondary database-driven mixed-methods study surveys from 273 women-led microentrepreneurs using a homogenous survey questionnaire and their enterprises throughout Bangladesh. The study employs primary responses from the women microentrepreneurs and utilized Ordinary Least Squares (OLS) and Ordered Logit (Ologit) regression to analyze the mutual relationship between the socio-economic development of women microentrepreneurs and the seven explanatory variables including four relevant control variables to meet the first research objective. The study has also used a paired t-test methodology to meet the second research objective, comparing the microenterprises’ three years’ average net income before and after taking microfinance. The results reveal that microfinance has a significant impact on their socio-economic development where all the independent variables except Q4IV and control variable Q8CV have shown significant relation with dependent variable. Additionally, the study confirms a statistically significant relationship between microfinance and the financial performance of those microenterprises. The study contributes to the field of research with a mixed-methods statistical facility to analyze microfinance’s impact on both socio-economic and financial performance dimensions of women microentrepreneurs using both primary and secondary data. JEL Classification Codes: G21, O16, J16, L26.